2022
DOI: 10.2495/tdi-v6-n2-197-207
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Of The Cost Of Paid Parking For Private Cars And Public Transport Fare On The Structure Of Urban Mobility

Abstract: The experience of European cities shows that with the introduction of free-fare public transport, the share of public transport trips increases insignificantly, while the number of trips by individual transport, bicycle and on foot decreases. The most common way to reduce the number of trips by private cars is to introduce parking fees and regulate the tariff. The paper examines the impact of public transport fare paid parking fees on the transport demand structure. The structure of transport demand is determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…One of the primary environmental benefits of introducing free public transport is the potential reduction in traffic congestion and vehicle emissions. By encouraging the public to switch from private cars to public transport, significant reductions in greenhouse gas emissions and other pollutants could be achieved, improving air quality and contributing to a healthier urban environment (Fadyushin and Zakharov, 2022;Sinha et al, 2019). This transition aligns with global efforts to combat climate change and local initiatives aimed at improving air quality in Croatian cities.…”
Section: Concept Of Free Public Transport In the Republic Of Croatiamentioning
confidence: 98%
See 1 more Smart Citation
“…One of the primary environmental benefits of introducing free public transport is the potential reduction in traffic congestion and vehicle emissions. By encouraging the public to switch from private cars to public transport, significant reductions in greenhouse gas emissions and other pollutants could be achieved, improving air quality and contributing to a healthier urban environment (Fadyushin and Zakharov, 2022;Sinha et al, 2019). This transition aligns with global efforts to combat climate change and local initiatives aimed at improving air quality in Croatian cities.…”
Section: Concept Of Free Public Transport In the Republic Of Croatiamentioning
confidence: 98%
“…The debate on the effectiveness and limitations of free urban public transport continues (Dydkowski and Gnap, 2019). Fadyushin and Zakharov (2022) emphasize that the transition to free public transport may only result in a modest increase in public transport usage, accompanied by a reduction in individual trips by mode of transport. Studies using multimodal transport models have identified a significant shift towards public transport after the adoption of free fare policies, consequently reducing the use of private cars (Kilani et al, 2022).…”
Section: Concept Of Free Public Transport Abroadmentioning
confidence: 99%